Penentuan Fase Kritis Tanaman Kacang Panjang (Vigna sinensis L.) terhadap Infeksi Bean Common Mosaic Virus (BCMV) - OCTAVIANI, NI LUH; SUDANA, I MADE; PHABIOLA, TRISNA AGUNG (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.1, Januari 2017, 2017)
Determine of the Critical Phase of Long Bean Plants (Vigna sinensis L.) against Infection of Bean Common Mosaic Virus (BCMV) This study aims to search the critical phase of long bean plants (Vigna sinensis L.) against infection of Bean Common Mosaic Virus (BCMV). The method used is Indirect ELISA (Indirect enzyme-linked immunosorbent assay). This research activity includes variations of symptoms on the long bean plants samples, the incidence of the disease, calculation of yields, the determination of the critical times of the plant, Indirect ELISA serology testing, and data analysis. Design used was a randomized block design (RBD) with seven treatments and four replications.The results showed that the variation of symptoms long bean plants infected BCMV that mosaic, vein banding, malformation of the leaves, stunted and chlorosis. Higher incidence of disease inoculation treatment 2 weeks after planting (WAP) is 91%. Long bean plants are attacked by BCMV the highest yield losses amounted to 93.54% at 2 WAP, so the critical phase of the plant is on the treatment of long bean 2 WAP. Based on these studies need to be done at the beginning of growth and, if already infected plants in early growth, eradication needs to be done so as not to be a source of inoculum.
Keywords: critical phase, BCMV, long beans